A feminilidade que se aprende : a educação através da moda na Revista do Globo/RS (1929-1939) - Scholl, Raphael Castanheira (2016)
The study aims to analyze the fashion sections and social life of an illustrated printed, founded in 1929, in Porto Alegre/RS, named Revista do Globo, biweekly draft circulated by the year 1967. We sought to understand printed as a women's education device for a period of ten years since the journal's foundation in 1929 until the year 1939, period covering the first decade of print. In fashion pictures and social representations of women occupied a prominent place notably the question of clothing, which played the role of costume for the role of women in Porto Alegre scenario. The pictorial and textual devices presented in the fashion section were contrasted with sections related to society, bringing images of social life through events in Porto Alegre and in the cities of the state or snapshot; photos taken in the city center. The relationship between objective sections tell whether women who appeared in social scenes showed, through the use of costumes, one prägnanz relationship with fashion images projected by the magazine. The representations of femininity and civility were analyzed using a transdisciplinary methodological exercise, the use of a historical and cultural approach. Thus, one can articulate the idea that the fashion section of the Revista do Globo, in its imagery and textual materiality, not only restricted the disclosure of clothing styles, but fulfilled the role of forming speech directed to the reader about well dressed as constituent elements of femininity and civility. The magazine thus conveyed an ideal through the images of fashion and photographic images of women in society, enrolled in classes of bourgeois elite of Rio Grande do Sul, at the time can be considered feminine representations of epoch, they were perceived as recipients of fashion and civility speeches. Whereas women who appeared in the social section were readers of the printed, verified the existence of a didactic fashion, where the suit was considered a key element for the representation of femininity that is learned.